2004
DOI: 10.1038/sj.jea.7500336
|View full text |Cite
|
Sign up to set email alerts
|

Comparing exposure metrics in the relationship between PM2.5 and birth weight in California

Abstract: Although studies suggest that air pollution is linked to perinatal outcomes, the geographic characterization of exposure to pollution differs between the studies. We compared neighborhood-and county-level measures of air pollution exposure, while examining the association between particulate matter less than 2.5 mm in aerodynamic diameter (PM 2.5 ) and birth weight among full-term births in California in 2000. To reduce the effects of demographic variability, our analysis was limited to two populations of 8579… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
3
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 20 publications
(28 reference statements)
5
47
3
1
Order By: Relevance
“…We found that differences in the geographic linkage method did not lead to large differences in the association between health status and PM 2.5 pollution. That the adjusted ORs calculated for the 5-mile study samples were somewhat smaller than those calculated using the broader exposure areas (Table 5) is consistent with the findings of Basu et al (2004) and does not support the hypothesis that more precise measurements lead to stronger associations. However, it is unclear whether the results in Table 5 are due to differences in study sample or differences in exposure assignment.…”
Section: Article In Presssupporting
confidence: 75%
See 2 more Smart Citations
“…We found that differences in the geographic linkage method did not lead to large differences in the association between health status and PM 2.5 pollution. That the adjusted ORs calculated for the 5-mile study samples were somewhat smaller than those calculated using the broader exposure areas (Table 5) is consistent with the findings of Basu et al (2004) and does not support the hypothesis that more precise measurements lead to stronger associations. However, it is unclear whether the results in Table 5 are due to differences in study sample or differences in exposure assignment.…”
Section: Article In Presssupporting
confidence: 75%
“…Willis et al (2003) conducted a re-analysis of the American Cancer Society Study (ACS) and found stronger associations using exposures calculated at the county level than at the original metropolitan area level. In contrast, Basu et al (2004) compared county-level pollution exposure to exposure based on averaging pollution measurements within 5 miles of a mother's residence to assess PM 2.5 exposure and birth weight; the results of this California study showed a stronger effect for the county level compared to the 5-mile exposure measure. The consequences of using different geographic units of analysis have also been compared in studies of neighborhood characteristics on health (Krieger et al, 2002).…”
Section: Introductionmentioning
confidence: 49%
See 1 more Smart Citation
“…Multiple studies have reported the association of fine particulate matter (PM 2.5 ) with low birthweight and growth restriction. The results of these studies generally demonstrate positive associations with PM 2.5 either averaged over the full pregnancy period or averaged over specific trimesters or periods of pregnancy (Basu et al, 2004;Bell et al, 2007;Wilhelm and Ritz, 2005;Liu et al, 2007;Morello-Frosch et al, 2010;Parker et al, 2005;Rich et al, 2009). However, some studies have also reported null results (Brauer et al, 2008;Mannes et al, 2005;Darrow et al, 2011).…”
mentioning
confidence: 81%
“…438 -444 The effects of air pollution on various other birth outcomes are substantially less well established and understood. Nevertheless, there are a growing number of contemporary studies that have evaluated potential links between air pollution and birth weight, [445][446][447][448][449][450][451][452][453][454][455][456] premature birth, 449,456 -458 fetal growth, 459 -461 intrauterine mortality, 462 birth defects, 463 and lymphocyte immunophenotypes in cord and maternal blood at delivery. 464 Recent reviews of the literature dealing with air pollution and these various birth outcomes 441,442,444 generally suggest that there may be effects of ambient PM air pollution on these outcomes but that these effects are not well understood.…”
Section: Infant/birth Outcomesmentioning
confidence: 99%